Cyber Terrorism and Public Support for Retaliation – A Multi-Country Survey Experiment. Issue 2 (10th April 2022) - Shandler, Ryan; Gross, Michael L.; Backhaus, Sophia; Canetti, Daphna
Abstract: Does exposure to cyber terrorism prompt calls for retaliatory military strikes? By what psychological mechanism does it do so? Through a series of controlled, randomized experiments, this study exposed respondents (n = 2, 028) to television news reports depicting cyber and conventional terror attacks against critical infrastructures in the United States, United Kingdom and Israel. The findings indicate that only lethal cyber terrorism triggers strong support for retaliation. Findings also confirm that anger bridges exposure to cyber terrorism and retaliation, rather than psychological mechanisms such as threat perception or anxiety as other studies propose. These findings extend to the cyber realm a recent trend that views anger as a primary mechanism linking exposure to terrorism with militant preferences. With cyber terrorism a mounting international concern, this study demonstrates how exposure to this threat can generate strong public support for retaliatory policies, depending on the lethality of the attack.